Acute liver failure in two dogs following ingestion of cheese tree (Glochidion ferdinandi) roots. Issue 2 (2nd December 2018) - Griebsch, Christine; Whitney, Joanna; Angles, John; Bennett, Peter
Abstract: Objective: To describe the management and resolution of acute liver failure (ALF) in two dogs following ingestion of cheese tree ( Glochidion ferdinandi ) roots. Case Summaries: A 2‐year‐old male entire Bullmastiff and a 5‐year‐old female neutered German Shepherd dog were presented for acute‐onset lethargy and vomiting after chewing on tree roots of a cheese tree. Both dogs developed clinical abnormalities consistent with ALF, including hepatic encephalopathy, marked increase in alanine aminotransferase activity and bilirubin concentration, and prolonged coagulation times. Treatment included administration of intravenous fluids, hepatoprotectants, vitamin K1, antibiotics, lactulose, antacids, antiemetics, and multiple fresh frozen plasma transfusions. Follow‐up examinations performed 30 days after initial presentation revealed the dogs to be clinically healthy with serum biochemical and coagulation profiles within reference intervals. New or Unique Information: This is the first report describing ALF in two dogs following ingestion of cheese tree ( G. ferdinandi ) roots. In this clinical setting, despite a poor prognosis, survival and recovery of adequate liver function were possible with medical management.